Gap Analysis and Strategy of Pt. Transportasi Jakarta in Improving Its Services Performance - Wisnu Surianugraha; Yusman Syaukat; Dwi Rachmina (School of Business, IPB University (SB-IPB), 2020)
PT. Transportasi Jakarta runs the Transjakarta services based on the standards that had been regulated as one of the variables for the financial support which is given from the Regional Government. As stated in the Governor Regulation Number 62 of 2016 and Governor Regulation Number 33 of 2017, the Regional Government needs to evaluate the performances of the company to fulfill the service standards considering the implementations of fines that will be applied if the standards did not achieve, thus the financial support will be ineffective and inefficient. The purpose of this study is to analyze the performance of PT. Transportasi Jakarta in attaining its Minimum Services Standards, and to develop the strategies to improve its service performance. The study uses Gap Analysis with secondary data from the Evaluation Report of Transjakarta Services in the Fourth quarter of 2018, and Analytical Hierarchy Process with primary data from the questionnaire given to respondents from all the related stakeholders. The result of this study shows that the performance of PT. Transportasi Jakarta has not yet reached the Minimum Service Standards. To improve the performance, the basic safety service needs to be prioritized by implementing a human resource development program. This could include open recruitment, capacity building, key performance indicators, and remuneration system. The renewal, mobilization of Transjakarta fleets, and integrated control system become the next strategy to improve punctuality since this type of service had the biggest fines applied and as the core service of Transjakarta services in providing mass transportations. Keywords: transjakarta, minimum service standard, gap analysis, analytical hierarchy process